Construct Validity of the Functionally Simulated Technology Task: An Exploratory Study. Issue 4 (1st October 2013) - Cardell, Beth; Swain, Larissa J.; Burnett, Amanda
ABSTRACT This study explored the construct validity of the Functional Simulated Technology Task (FSTT), online bill-pay version. The FSTT was administered to matched groups: persons with cognitive impairment and persons with no known cognitive impairment, established through the Montreal Cognitive Assessment (MoCA). Results indicated significance for construct validity by discriminating between the two groups. Results also indicated a good to excellent positive relationship between scores on the MoCA and the FSTT score areas of Outcome, Quality, Process, and Independence. The findings support the use of the FSTT to measure executive function using a simulated online bill-pay task.